Standardization of Dolphin Cardiac Auscultation and Characterization of Heart Murmurs in Managed and Free-Ranging Bottlenose Dolphins (Tursiops truncatus) - Linnehan, Barbara K.; Hsu, Adonia; Gomez, Forrest M.; Huston, Sharon M.; Takeshita, Ryan; Colegrove, Kathleen M.; Rowles, Teri K.; Barratclough, Ashley; Musser, Whitney B.; Harms, Craig A.; Cendejas, Veronica; Zolman, Eric S.; et al. (Frontiers in Veterinary Science, 2020)
Cardiac auscultation is an important, albeit underutilized tool in aquatic animal medicine due to the many challenges associated with in-water examinations. The aims of this prospective study were to (1) establish an efficient and repeatable in-water cardiac auscultation technique in bottlenose dolphins (Tursiops truncatus), (2) describe the presence and characterization of heart murmurs detected in free-ranging and managed dolphins, and (3) characterize heart murmur etiology through echocardiography in free-ranging dolphins. For technique development, 65 dolphins cared for by the Navy Marine Mammal Program (Navy) were auscultated. The techniques were then applied to two free-ranging dolphin populations during capture-release health assessments: Sarasota Bay, Florida (SB), a reference population, and Barataria Bay, LA (BB), a well-studied population of dolphins impacted by the Deepwater Horizon oil spill. Systolic heart murmurs were detected at a frequent and similar prevalence in all dolphin populations examined (Navy 92%, SB 89%, and BB 88%), and characterized as fixed or dynamic. In all three populations, sternal cranial and left cranial were the most common locations for murmur point of maximal intensity (PMI). An in-water transthoracic echocardiogram technique was refined on a subset of Navy dolphins, and full echocardiographic exams were performed on 17 SB dolphins and 29 BB dolphins, of which, 40 had murmurs. Spectral Doppler was used to measure flow velocities across the outflow tracts, and almost all dolphins with audible murmurs had peak outflow velocities ≥1.6 m/s (95%, 38/40); three dolphins also had medium mitral regurgitation which could be the source of their murmurs. The presence of audible murmurs in most of the free-ranging dolphins (88%) was attributed to high velocity blood flow as seen on echocardiography, similar to a phenomenon described in other athletic species. These innocent murmurs were generally characterized as Grade I-III systolic murmurs with PMI in the left or sternal cranial region. This study is the first to describe an efficient technique for in-water dolphin cardiac auscultation, and to present evidence that heart murmurs are common in bottlenose dolphins.